Characterising of kuantan bauxite soil for geotechnical assessment and its suitability for foundation design - Noorul Iqhlima Najwa, Ismail (2024)
Lateritic bauxite is a unique type of soil deposit commonly found in the vicinity of development areas in Kuantan, which is located on the east coast of Malaysia. Despite active bauxite mining since 2015, doubts persist regarding this land deposit's engineering characteristics and suitability as a foundation. This research aims to characterise the properties of bauxite soil deposits using established methods in geotechnical engineering. This includes developing a modified friction angle equation based on the M value and designing the bearing capacity to evaluate the geotechnical suitability of the bauxite soil deposits as a foundation. Soil samples were taken from former bauxite mining areas, including Semambu, Bukit Goh and Indera Mahkota. The Mackintosh Probe M-values were converted to corrected N-values to develop a modified friction angle equation. Soil samples were tested in the laboratory according to the standards of soil characterisation analysis and evaluated based on particle size distribution, porosity, permeability, erodibility index, moisture content, specific gravity, bulk density, saturated unit weight and strength parameters. Based on the investigation of the soil properties, the particle size analysis revealed a minimum size of 0.06 mm and a maximum of 10 mm, thus proving the soil to be a well-graded SAND. The XRF tests confirmed a low silica content of 2% to 21%, which indicates high bauxite activity. The significantly high sesquioxide content, ranging from 13% to 45%, justifies the sesquioxides acting as binders, which hold soil particles firmly. These sesquioxides are insoluble in water and contribute to relatively high soil strength that results in friction angles in the range of 19° to 45°. However, the erodibility index on the upper horizon is classified as extremely high, necessitating surface rehabilitation and stabilisation if structures or slopes are to be constructed on the soil surface. Moreover, the developed modified friction angle equation (ϕ=0.024M+28.768) can be utilised to design the bearing capacity in former bauxite mining areas and ground characterised as graded SAND. It is found that, with range friction angles of 33° to 45°, the highest allowable bearing capacity and highest ultimate bearing capacity is 1208 kPa and 3500 kPa respectively as refer to Table 5.6. In conclusion, based on the bearing capacity design, bauxite soil deposits in Kuantan are suitable and should be redeveloped